2009
DOI: 10.1016/j.exphem.2009.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of STAT3 and GATA-1 interactions in γ-globin gene expression

Abstract: Objective-We previously demonstrated a silencing role for Stat3 in γ-globin gene regulation in primary erythroid cells. Recently GATA-1, a key transcription factor involved in hematopoietic cell development was shown to directly inhibit the activity of Stat3 in vivo. Therefore we completed studies to determine if interactions between these two factors influence γ-globin gene expression.Methods-Chromatin immunoprecipitation (ChIP) assay was used to ascertain in vivo protein binding at the γ-globin 5'untranslate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…60 Furthermore, as erythroid differentiation progresses, erythropoietin has the ability to activate STAT3 through serine 727 phosphorylation 62 as g-globin gene silencing occurs. Consistent with these observations, miR-34a overexpression induced HbF and reduced totaland phosphorylated-STAT3 levels in K562 stable clones.…”
Section: Discussionmentioning
confidence: 99%
“…60 Furthermore, as erythroid differentiation progresses, erythropoietin has the ability to activate STAT3 through serine 727 phosphorylation 62 as g-globin gene silencing occurs. Consistent with these observations, miR-34a overexpression induced HbF and reduced totaland phosphorylated-STAT3 levels in K562 stable clones.…”
Section: Discussionmentioning
confidence: 99%
“…S4D). Previous studies have shown that formation of the STAT3-GATA1 complex leads to the inhibition of the expression of c-globin (Ezoe et al, 2005;Foley et al, 2002;Kirito et al, 1998;Yao et al, 2009). Furthermore, the Krüppel-type zinc finger transcription factor ZBP-89 has been previously reported to interact with GATA1 and regulate expression of the globin genes and erythroid differentiation during hematopoiesis in zebrafish (Li et al, 2006;Ohneda et al, 2009;Woo et al, 2011;Woo et al, 2008).…”
Section: Ptpn9 Is Required For Erythroid Cell Maturationmentioning
confidence: 99%
“…Previous studies have elucidated that phosphorylated STAT3 inhibits GATA1 through a direct protein-protein interaction (Ezoe et al, 2005;Yao et al, 2009). The ability of phosphorylated STAT3 to suppress GATA1 transactivation has been attributed to the alteration of GATA1 binding stability.…”
Section: Dephosphorylation Of Stat3 By Ptpn9 Contributes To Erythroidmentioning
confidence: 99%
See 1 more Smart Citation
“…69 In subsequent studies, we observed in vivo binding of STAT3 and GATA-1 to this region by chromatin immunoprecipitation assay in K562 and mouse erythroleukemia cells. 70 DNA- 75 Lou et al, 77 Ikuta et al, 93 Tang et al 96 Butyrate HDAC inhibitor p38, cGMP, cAMP Witt et al, 71 Pace et al, 78 Sangerman et al 81 Trichostatin protein interaction studies confirmed that a STAT3/GATA-1 complex is assembled in this region. STAT3b enforced expression in K562 cells reduced g-globin expression which was reversed by GATA-1 over-expression.…”
Section: Jak/stat Signaling Pathwaymentioning
confidence: 79%